Intervening decision-making in using alternative dispute resolutions: A parsimonious intervention model - Lee, Chia Kuang; Yiu, Tak Wing; Cheung, Sai On (Springer Nature, 2022)
Extending the concept of Technology Acceptance Model (TAM). This study develops a parsimonious alternative dispute resolution intervention model. Experts’ opinions suggested normative pressures (NP) and trust (TR) are influencing forces in shaping attitude. Intervention is most effective in two situations (i) when a dispute surfaces; and (ii) during claim negotiation but before the dispute crystalises. In addition, effective interventions for ADR use could include ADR campaigns and highlighting ADR values. Favourable normative pressures (NP) and trusts (TR) would therefore then lead to a favourable attitude (ATT) and increase the overall intention (INT) to use ADR through the interactions of perceived ease of use (PE) and relative advantage (PA) with attitude (ATT).